Peradaban Islam Di Nusantara Masa Penjajahan Dan Perkembangan Pendidikan - Kunti Fatimah; Nazila Ramadhaniyah; Zakiyautul Mizkiyah (Universitas Negeri Gorontalo, 2026)
This article aimed to re-examine the development of Islamic civilization in the Nusantara through the lens of education during the Dutch colonial period. The colonial era was a crucial period in which Islamic education underwent a transformation from the traditional pesantren system into a more structured madrasah system as a response to the secular education policies of the Dutch East Indies government. Through a literature review of previous studies, it was found that Islamic education played a dual role: as an institution for religious transmission and as an instrument of cultural resistance. The results of the review indicated that discriminatory Dutch policies, such as the Teacher Ordinance and the Wild School Ordinance, in fact triggered internal modernization within Islamic organizations such as Muhammadiyah and Nahdlatul Ulama. Islamic civilization in the Nusantara during this period did not collapse; rather, it formed a new synthesis between traditional values and modern educational management, which became the foundation for Indonesia’s national education system after independence.